THE MAIN APPROACHES OF PURCHASE PLANNING ON THE BASIS OF SYSTEM SAP R/3 WITH REGARD TO WORKING CONDITIONS OF RUP «BMZ» - E. V. Osadchaja; E. F. Terletskaja (Литьë и металлургия, 2011)
The basic approaches of automation of purchase planning on the basis of the system SAP R/3 for RUP «BMZ» are considered.